SOURCES OF FORMATION OF TARAS SHEVCHENKO’S CULT IN EASTERN HALYCHINA - Нагачевська, З. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article studies sources of formation of Taras Shevchenko’s cult as a key personality in Eastern Halychyna, proves that the poet’s name performed here not only the role of the artist words – enlightener, but also the waker of Ukrainians’ national feelings.